Provably good multiprocessor scheduling with resource sharing - Andersson, Björn (2014)
We present a 12(1 + 3R/(4m)) competitive algorithm for scheduling implicit-deadline sporadic tasks on a platform comprising m processors, where a task may request one of R shared resources.